Grapevine bacterial canker in the State of São Paulo, Brazil: detection and eradication - Rodrigues Neto, Júlio; Destéfano, Suzete A. L.; Rodrigues, Lucas M. R. [UNESP]; Pelloso, Danilo Souza; Oliveira Júnior, Leonardo da Cruz (Sociedade Brasileira de Fitopatologia, 2011)
Sintomas do cancro bacteriano da videira na variedade Red Globe foram observados em agosto de 2009 em pomar de Tupi Paulista, Estado de São Paulo, Brasil, e o agente causal Xanthomonas campestris pv. viticola foi identificado por meio de testes patológicos e moleculares. O procedimento de erradicação foi adotado e aproximadamente 4.700 plantas foram destruídas. Um levantamento realizado nas regiões produtoras do Estado de São Paulo não encontrou nenhum outro pomar contaminado, e essa espécie bacteriana é considerada ausente neste estado.

Symptoms of bacterial canker of grapevine in the variety Red Globe were observed in August 2009 in an orchard at Tupi Paulista, São Paulo State, Brazil, and the causal agent Xanthomonas campestris pv. viticola was identified by pathological and molecular tests. Eradication procedure was adopted and approximately 4,700 plants were destroyed. A survey was conducted on grape-producing regions in the state of São Paulo, which found no other contaminated orchard, and this bacterial species is considered absent in the state.
Cancro bacteriano da videira no Estado de São Paulo: detecção e erradicação
Keywords: Xanthomonas campestris pv. viticola; levantamento; PCR-RFLP; Xanthomonas campestris pv. viticola; survey; PCR-RFLP